STUDI POTENSI EMBUNG SUB WILAYAH SUNGAI WATUTELA WUNO DI WILAYAH KOTA PALU DAN KABUPATEN DONGGALA SULAWESI TENGAH - Sutapa, I Wayan (MEKTEK, 2008)
Regional river of Watutela Wuno which is located in Palu and Donggala Regency in Central Sulawesi represent the valley area encircled by mountain with many river emit a stream of among other things later on have estuary to Palu river. The river is very potential developed as water resource to fulfill amount of water required of resident especially at dry season by developing a dam. This study is to know the potential river or location to be made dam location to fulfilling amount of water required resident, livestock and garden and also know the amount water availability at the river. Method used by data collecting from related institution, survey field and analyze the condition of location of candidate dam and also test the sensitivity to determine the development priority. From the analysis got that Ngia dam in Ngatabaru village most important to can be developed with the consideration of various aspects.